Potensi Pendapatan Pajak Hiburan Dan Kontribusinya Terhadap Pendapatan Asli Daerah Pada Badan Pendapatan Daerah Kabupaten Bulukumba - sudirman sudirman; Azwar Wijaya Syam (Economy Deposit Journal (E-DJ), 2021)
This study aims to determine the potential for entertainment tax revenue and its contribution to local revenue at the Bulukumba Regency Regional Revenue Agency. The research method used is descriptive research with a quantitative approach, secondary data sources are the Budget Report and Realization of Regional Original Revenue, Entertainment Tax managed by the Regional Revenue Agency of Bulukumba Regency from 2018 to 2020. To find out about the potential, effectiveness and contribution of revenue entertainment tax in Bulukumba district. This research was conducted from April 22, 2021 to May 22, 2021. The results show that the potential for entertainment tax in 2018-2020 fluctuates, namely increasing and decreasing for the period 2018 - 2021. The effectiveness of entertainment tax revenues in Bulukumba district is less effective because each year it does not exceed the target. The contribution of the entertainment tax to the Bulukumba district's local tax revenue is very low because there are still many entertainment venues that have not been taxed and are also affected by restrictions on community activities due to the COVID-19 pandemic which can lead to a decrease in the contribution of entertainment taxes to Bulukumba district's income. Efforts to increase entertainment tax revenue and its contribution to local revenue at the Bulukumba Regency Regional Revenue Agency can be done by counseling the public or taxpayers about the importance of paying taxes for regional development and it is better if the organizers of entertainment venues that have not been confirmed as taxpayers are immediately confirmed as taxpayers. taxpayer.